2016
DOI: 10.1177/0885328216647197
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic efficacy of strontium hydroxyapatite micro-granules in osteoporotic rat model

Abstract: Excessive demineralization in osteoporotic bones impairs its self-regeneration potential following a defect/fracture and is of great concern among the aged population. In this context, implants with inherent osteogenic ability loaded with therapeutic ions like Strontium (Sr) may bring forth promising outcomes. Micro-granular Strontium incorporated Hydroxyapatite scaffolds have been synthesized and in vivo osteogenic efficacy was evaluated in a long-term osteoporosis-induced aged (LOA) rat model. Micro-granules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…The obtained microgranules were characterized using XRD and SEM methods and were further implanted in nine osteoporotic rats, being evaluated by Micro-CT . After explantation, the newly bone formed in presence of 10%SrHA microgranules and presented a density comparable to the host native tissue [44]. The explants with HA microgranules exhibited a slight decrease in bone density, fact supporting the idea that such composition may be used in the treatment of the osteoporotic bones [44].…”
Section: Strontium (Sr)-hydroxyapatite Based Composites For Btementioning
confidence: 69%
See 1 more Smart Citation
“…The obtained microgranules were characterized using XRD and SEM methods and were further implanted in nine osteoporotic rats, being evaluated by Micro-CT . After explantation, the newly bone formed in presence of 10%SrHA microgranules and presented a density comparable to the host native tissue [44]. The explants with HA microgranules exhibited a slight decrease in bone density, fact supporting the idea that such composition may be used in the treatment of the osteoporotic bones [44].…”
Section: Strontium (Sr)-hydroxyapatite Based Composites For Btementioning
confidence: 69%
“…In vivo studies were conducted by Chandran et al, in two different species: osteoporotic sheep and rat models. [44][45]. First, they fabricated microgranules of 10% SrHA (with the chemical formula Ca 9 Sr 1 (PO 4 ) 6 (OH) 2 ) and simple HA (used as control), in order to assess the osteogenic potential and the osteointegration speed.…”
Section: Strontium (Sr)-hydroxyapatite Based Composites For Btementioning
confidence: 99%
“…Results obtained from the evaluation of osteogenic potential of Sr incorporated HA micro-granules are in line with these evidences. Chandran et al demonstrated in a long-term OP-induced aged model that the combination of Sr and highly porous HA promotes complete bone healing, showing a regeneration efficacy higher than the HA group, also confirmed by microCT evaluation of the trabecular bone status [37].…”
Section: Rat Modelmentioning
confidence: 82%
“…Impaired proliferation and differentiation potential of resident mesenchymal stem cells and induction factors have been reported to delay bone healing 29 . In short term-induced models, delay in fracture healing is attributed to the accelerated resorption by osteoclast cells resulting in bone loss, but these models lack the reduction in osteogenic capacity of the bone-forming cells 30 . Conversely, in our study impaired osteogenic potential was evident in the long term induced osteoporotic model by 8 weeks, whereas the Control rats exhibited a complete bridging of the defect.…”
Section: Discussionmentioning
confidence: 99%